2020
DOI: 10.1016/j.radcr.2020.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Intralobar pulmonary sequestration: incidental finding in an asymptomatic patient

Abstract: We describe a case of a 58-year-old male who presented to the emergency room with symptoms related to an appendicitis. A computed tomography scan with contrast confirmed the diagnosis of acute appendicitis but also revealed a mass medially in the base of the inferior lobe of the right lung. The mass measured 6.7 cm AP × 3.7 cm transverse. It had multiple lobulations and the anterior aspect was of very low density, possibly representing accumulated mucoid material. The mass had an arterial connection from the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Most patients with pulmonary sequestration have infectious manifestations, such as cough and expectoration, fever, chills, hemoptysis, and chest pain. Some patients have no obvious symptoms and are diagnosed only during physical examination 8,17–19 . Studies have found that patients with intralobar pulmonary sequestration are mainly infected, whereas those with extralobar pulmonary sequestration are mostly found during physical examination 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients with pulmonary sequestration have infectious manifestations, such as cough and expectoration, fever, chills, hemoptysis, and chest pain. Some patients have no obvious symptoms and are diagnosed only during physical examination 8,17–19 . Studies have found that patients with intralobar pulmonary sequestration are mainly infected, whereas those with extralobar pulmonary sequestration are mostly found during physical examination 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Some patients have no obvious symptoms and are diagnosed only during physical examination. 8 , 17 , 18 , 19 Studies have found that patients with intralobar pulmonary sequestration are mainly infected, whereas those with extralobar pulmonary sequestration are mostly found during physical examination. 12 Among the 10 patients with intralobar pulmonary sequestration in this study, six were diagnosed with cough, sputum, chest pain, or hemoptysis, and four were diagnosed by physical examination.…”
Section: Discussionmentioning
confidence: 99%